(The Study on The Effects of Isolation Time and Identification for Lemon (Citrus Limon Burm. F.) Oil Leather and Its Apllication on Soft Drinks) - Enny Hawani Lubis; Ngakan Timur Antara; Rizal Alamsyah (Balai Besar Industri Agro, 2004)
The objectives of this research were(1)to study the effects of fixation time on distillation for lemon leather,(2) to investigate chemical composition of lemon oil (flavor),and (3)to apply lemon flavor on soft drink simulation .the method used in resulting lemon oil was water-steam distillation continued by the second 3 hours .the results show that lemon oil produced during the fist there hours distillation was higher (1.738%) than those resulted from the second three hours distillation (o.701%) based on gas chromatography test,lemon oil resulted contain a-pinen,b-pinen,limonen, linalool and sitral (neral and gerenial) these were identified by measuring peak enrichment three formulas were used on the application of lemon oil or flavor on soft drink namely (1)mixture of cellulose microcrystalline ,sorbitol,and lemon oil (2) mixture of cellulose microcystalline ,sucrose and lemon oil and (3)whey powder,tricalcium phosphat,and lemon oil .based on the organoleptic test and larmond scale the preferred soft drink was from cellulose microcystalline, sorbitol, and lemon oil. with citric oil additions.